2012
DOI: 10.1111/j.1528-1167.2012.03651.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid loading of intravenous lacosamide: Efficacy and practicability during presurgical video‐EEG monitoring

Abstract: SUMMARYPurpose: This study investigates immediate efficacy and safety of intravenous application of de novo lacosamide (LCM) as add-on therapy in patients with pharmacoresistant focal epilepsy. Methods: During presurgical video-electroencephalography (EEG) monitoring, 17 adult inpatients received LCM infusion (200 mg every 12 h for 2-3 days) followed by oral formulation with the same regimen. Before and after intravenous application of LCM, seizures and interictal epileptiform discharges (IEDs) recorded with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
1
4
0
3
Order By: Relevance
“…In addition, these LCM-treated epileptic rats had a significant smaller number of seizures. Our results are in line with clinical studies showing that LCM has anti-ictogenic properties in patients with partial-onset seizures (Chung et al, 2010;Li et al, 2013); however the percentage of patients reaching seizure control in placebo-controlled trials does not exceed 50%. The pilocarpine model of MTLE is known to reproduce the level of pharmacoresistance that is characteristic of this epileptic syndrome (Curia et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, these LCM-treated epileptic rats had a significant smaller number of seizures. Our results are in line with clinical studies showing that LCM has anti-ictogenic properties in patients with partial-onset seizures (Chung et al, 2010;Li et al, 2013); however the percentage of patients reaching seizure control in placebo-controlled trials does not exceed 50%. The pilocarpine model of MTLE is known to reproduce the level of pharmacoresistance that is characteristic of this epileptic syndrome (Curia et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…To date, no study has specifically explored the effect of LCM on interictal spikes in patients with MTLE. However, in patients with pharmacoresistant focal epilepsy, Li et al (2013) found a nonsignificant reduction of interictal epileptiform activity after acute intravenous LCM treatment, whereas no effect were observed by Giorgi et al (2013) following adjunctive per os treatment with LCM. Moreover, it has been reported in the perforant path stimulation model that LCM induces a decrease in interictal spike rates in the dentate gyrus 6 weeks after SE (Wasterlain et al, 2011).…”
Section: Discussionmentioning
confidence: 73%
“…In some studies, a tendency toward the reduction of IEDs incidence after acute [49] and chronic administration [50] in small samples of patients with focal epilepsy has been reported, even though the results were not statistically significant and the patient samples were too small to allow clear conclusions.…”
Section: Lacosamidementioning
confidence: 91%
“…Single-blind, placebocontrolled, crossover 10 min EEG before and each 3 h for 7 times after drug administration PHT reduces IEDs [21] Kellaway et al No effect of LCM on IEDs [49] Giorgi et al [18] Gobbi et al PHT > sulthiame; no statistically significant results [23] Jawad et al Effects of antiepileptic drugs on interictal epileptiform discharges in focal epilepsies Review informahealthcare.com EEG investigations during therapy with carbamazepine' [14]. Actually, reconsidering these reports according to current knowledge, IEDs worsening was limited to patients with IGE, a phenomenon repeatedly confirmed thereafter [15].…”
Section: Carbamazepinementioning
confidence: 99%
“…In addition, lacosamide, a potent anti‐ictogenic drug in the pilocarpine animal model, was capable of decreasing interictal spike rates in temporal lobe regions of pilocarpine‐treated rats (Behr et al ., ). In epileptic patients, however, lacosamide induced no effect or only a non‐significant decrease in interictal spiking activity (Giorgi et al ., ; Li et al ., ).…”
Section: Modulation Of Interictal Oscillations By Anticonvulsantsmentioning
confidence: 97%